Characterization of Individuals with Sacroiliac Joint Bridging in a Skeletal Population: Analysis of Degenerative Changes in Spinal Vertebrae. (8th September 2014) - Imamura, Takeshi; Saiki, Kazunobu; Okamoto, Keishi; Maeda, Junichiro; Matsuo, Hiroaki; Wakebe, Tetsuaki; Ogami, Keiko; Manabe, Yoshitaka; Koseki, Hironobu; Tomita, Masato; Tagami, Atsushi; Osaki, Makoto; et al.
Abstract : The aim of this study was to characterize the individuals with sacroiliac joint bridging (SIB) by analyzing the degenerative changes in their whole vertebral column and comparing them with the controls. A total of 291 modern Japanese male skeletons, with an average age at death of 60.8 years, were examined macroscopically. They were divided into two groups: individuals with SIB and those without bridging (Non-SIB). The degenerative changes in their whole vertebral column were evaluated, and marginal osteophyte scores (MOS) of the vertebral bodies and degenerative joint scores in zygapophyseal joints were calculated. SIB was recognized in 30 individuals from a total of 291 males (10.3%). The average of age at death in SIB group was significantly higher than that in Non-SIB group. The values of MOS in the thoracic spines, particularly in the anterior part of the vertebral bodies, were consecutively higher in SIB group than in Non-SIB group. Incidence of fused vertebral bodies intervertebral levels was obviously higher in SIB group than in Non-SIB group. SIB and marginal osteophyte formation in vertebral bodies could coexist in a skeletal population of men. Some systemic factors might act on these degenerative changes simultaneously both in sacroiliac joint and in vertebral column.